2022
DOI: 10.1007/s10551-022-05245-4
|View full text |Cite
|
Sign up to set email alerts
|

A Virtual Net Locks Me In: How and When Information and Communication Technology Use Intensity Leads to Knowledge Hiding

Abstract: The research explores a novel phenomenon in which information and communication technology (ICT), which is originally designed for knowledge transferring, may result in employees’ knowledge hiding due to increasing use intensity. Specifically, drawing upon the appraisal theory of empathy, we develop a moderated mediation model of empathy linking ICT use intensity and knowledge hiding. The hypothesized model is tested by conducting a scenario-based experimental study (Study 1, N = 194) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Our findings show that nonworking time ICT demands can be resource-depleting, which leads employees to adopt knowledge hiding. Not only does this help us grasp that employees engage in knowledge hiding as a response to the threat of resources in the private domain (Halbesleben et al , 2014), but the shift from workplace antecedents of daily working hours to those of personal leisure time has also assisted us in developing a cross-domain perspective for a more comprehensive understanding of knowledge hiding (Zhang and Ji, 2022). In particular, the discrepancy between the results of the study on DKH and rationalized hiding has further supported the argument that different motivations exist for the various dimensions of knowledge hiding (He et al , 2023), which encourages us to investigate the formation mechanisms of knowledge hiding through a more accurate and effective theoretical lens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings show that nonworking time ICT demands can be resource-depleting, which leads employees to adopt knowledge hiding. Not only does this help us grasp that employees engage in knowledge hiding as a response to the threat of resources in the private domain (Halbesleben et al , 2014), but the shift from workplace antecedents of daily working hours to those of personal leisure time has also assisted us in developing a cross-domain perspective for a more comprehensive understanding of knowledge hiding (Zhang and Ji, 2022). In particular, the discrepancy between the results of the study on DKH and rationalized hiding has further supported the argument that different motivations exist for the various dimensions of knowledge hiding (He et al , 2023), which encourages us to investigate the formation mechanisms of knowledge hiding through a more accurate and effective theoretical lens.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, since the knowledge economy is driving organizations to rely extensively on ICTs for knowledge management (Pandey et al , 2021), emerging scholars have turned their attention to how the relevant use of ICTs affects employees’ knowledge hiding. For example, Zhang and Ji (2022) have found that high-intensity use of ICT for processing work can prevent employees from caring about their coworkers’ emotions, so they will engage in knowledge hiding. Meanwhile, Ma et al (2020) argue that using social media by employees with low job engagement increases the likelihood of knowledge hiding.…”
Section: Literature Reviewmentioning
confidence: 99%